2014
DOI: 10.1021/ic500387u
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Coordination and the Binding Sites of Cu2+by the Histidyl-6-Tag using Experimental and Computational Tools

Abstract: His-tags are specific sequences containing six to nine subsequent histydyl residues, and they are used for purification of recombinant proteins by use of IMAC chromatography. Such polyhistydyl tags, often used in molecular biology, can be also found in nature. Proteins containing histidine-rich domains play a critical role in many life functions in both prokaryote and eukaryote organisms. Binding mode and the thermodynamic properties of the system depend on the specific metal ion and the histidine sequence. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
74
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(87 citation statements)
references
References 60 publications
11
74
0
Order By: Relevance
“…Our previous studies on copper complexes with the His 6 -tag have shown similar results: the presence of polymorphic binding states (with the participation of maximum two His residues in metal ion binding) and the formation of helical structures for some binding modes. 12,13 Since our recent studies on the specificity of the metal ion interactions with His-tags containing 6 or 9 His residues have shown very unusual behavior and incredible efficiency of binding metal ions, 11,12,14 this work extends our studies to new analogues in which the His residues mutated to Ala residues. Therefore the aim of this study is to examine the properties and the structural characterization of these new poly-(His-Ala) analogues of the pHG peptide.…”
Section: Introductionmentioning
confidence: 66%
“…Our previous studies on copper complexes with the His 6 -tag have shown similar results: the presence of polymorphic binding states (with the participation of maximum two His residues in metal ion binding) and the formation of helical structures for some binding modes. 12,13 Since our recent studies on the specificity of the metal ion interactions with His-tags containing 6 or 9 His residues have shown very unusual behavior and incredible efficiency of binding metal ions, 11,12,14 this work extends our studies to new analogues in which the His residues mutated to Ala residues. Therefore the aim of this study is to examine the properties and the structural characterization of these new poly-(His-Ala) analogues of the pHG peptide.…”
Section: Introductionmentioning
confidence: 66%
“…Various approaches have been developed to describe the interactions between metal ions and coordinated residues in classical MD simulations, including nonbonded, semibonded, and bonded models. Cu 2+ bonded models already exist for the CHARMM force field,,, and a semibonded Cu 2+ model that includes the Jahn−Teller effect is available for the OPLS‐AA/L force field ,. More than twenty years ago, Hancock already used bonded models to study systems including copper and nickel ,.…”
Section: Methodsmentioning
confidence: 99%
“…The (1,2) connectivity is the only other type that allows all three metal atoms to be accommodated using identical connectivity patterns for all of them: (1,2/3,4/5,6). Since metal binding is known to induce alpha‐helical conformation within poly‐histidine sequences, we chose the alpha‐helix as the initial conformation of HHHHHH prior to introducing three ruthenium atoms (each coordinated to two tris (hydroxymethyl)‐aminomethane molecules in the O‐ cis /N‐ trans conformation) to the peptide. Both (1,4/2,5/3,6) and (1,2/3,4/5,6) configurations were constructed and energy‐minimized, followed by molecular dynamics (MD) simulations.…”
Section: Resultsmentioning
confidence: 99%
“…(1,2/3,4/5,6). Since metal binding is known to induce alpha-helical conformation within poly-histidine sequences, 35 Figure 8). The more compact, helix-like conformation of (1,4/2,5/3,6) is also more energetically favorable, with its energy calculated to be 127 kcal/mol lower compared with that of (1,2/3,4/5,6).…”
Section: A Hexa-histidine Peptide As a Polydentate Ruthenium (Iii) mentioning
confidence: 99%